Building up the Bounce Back League: Embedding trauma-informed sport interventions throughout a national youth community organization. - Shaikh, Majidullah (Université d'Ottawa | University of Ottawa, 2021)
Majidullah Shaikh, University of Ottawa: Building up the Bounce Back League: Embedding Trauma-Informed Sport Interventions throughout a National Youth Community Organization. Trauma-informed sport is intended to promote resilience and psychosocial development of youth at risk of exposure to traumatic experiences. Shaikh will discuss a collaborative partnership with Boys and Girls Clubs of Canada to scale-out such practices and programming across Canada.